Source material creation for high content of dry soluble substances F1 cherry tomato hybrids breeding - S. F. Gavrish; T. A. Redichkina; A. I. Topinskiy (Овощи России, 2022)
Relevance. Consumer demand development of exotic colors presence in modern tomato hybrids requires a timely response from domestic breeders for creating highly effective hybrids. With regard to cherry tomatoes, special attention of breeders is aimed at achieving excellent taste in new hybrids. One of the indicators is the "content of dry soluble substances in fruits". However, there is no information in the literature about the variation of this trait within different color groups of cherry tomatoes. The aim of our work was the creation of initial material for the selection of F1 cherry tomato hybrids with a high content of dry soluble substances.Materials and methods. All measurements were obtained by the refractometric method and presented in the oBrix scale. The study examined 46 F2 splitting cherry tomato populations, including 17 red, 12 yellow, 7 pink, 8 brown, and 2 purple. Analyzing the obtained data, the following statistical indicators were made: the frequency of occurrence of the variant; arithmetic mean; dispersion; the coefficient of variation; sample mean error. Relative error was used to test the sample results obtained.Results. The coefficients of variation of the trait «content of dry soluble substances in fruits» were calculated in each of the five color groups of cherry tomatoes (from 17.43% for brown-fruited to 25.13% for red-fruited). The boundaries of variability and average values of the content of dry soluble substances were determined both within the groups (from 7.2 oBr in pink-fruited to 8.8 oBr in yellow-fruited ones), and for each studied breeding sample. The practical result of the work was selection of the most promising breeding material within different color groups of cherry tomato, combining high values of dry matter with a complex of economically valuable traits.